Comparative Study on Clear Specimen Strength and Member Strength of Side-Pressure Laminated Bamboo - Danping Gao; Bowang Chen; Liu Wang; Chunan Tang; Ping Yuan (Advances in Civil Engineering, 2022)
Side-pressure laminated bamboo (LB) made from heat-modified, fast-growing bamboo is introduced in this document. As a relatively new type of bamboo composite fabricated by bamboo strips, side-pressure LB has some favorable mechanical properties, such as thermal insulation, light mass, high strength, and earthquake resistance. To promote the application of side-pressure LB in structural engineering, according to the test standards for timber, the mechanical properties of bamboo, including tensile strength parallel to the grain, compressive strength parallel to the grain, bending strength and bending modulus, and shear strength parallel to the grain, were obtained by testing clear bamboo. Meanwhile, the bending and shear tests were performed on full-sized beams of side-pressure LB. Comparing the strength of clear bamboo and full-sized bamboo beams under bending and shear, explore the effect of size on bending and shear strength. The results demonstrate that the size effect has a significant influence on the bending strength, and the bending strength decreases clearly with the increase of the span of member; the shear strength is mainly affected by the shear area and decreases with the increase of the shear area. Based on the measured indicators of shear strength, a formula suitable for converting the shear strength of clear bamboo to full-sized bamboo beam is proposed. And the recommended design strengths of bamboo are given by using the limit state method, which provides a design basis for the engineering application of bamboo.